2017
DOI: 10.1039/c7an01496a
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modification of antibodies enables the formation of stable antibody–gold nanoparticle conjugates for biosensing

Abstract: Antibody-modified gold nanoparticles (AuNPs) are central to many novel and emerging biosensing technologies due to the specificity provided by antibody-antigen interactions and the unique properties of nanoparticles. These AuNP-enabled assays have the potential to provide significant improvements in sensitivity and multiplexed analysis compared to conventional immunoassays. However, a major challenge for these AuNP platform technologies is the synthesis of stable antibody-AuNP conjugates that resist aggregatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 62 publications
1
35
1
Order By: Relevance
“…Most widely in literature, antibodies are functionalized via NHS-chemistry. [41][42][43] In this case, the functional group is attached on the lysine residues or the N-termini of the antibodies. This functionalization strategy is highly unspecific as lysine residues are distributed over the whole antibody sequence including the antigen-binding site (Fab region).…”
Section: Antibody Functionalization and Coupling To Liposomes Via Copmentioning
confidence: 99%
“…Most widely in literature, antibodies are functionalized via NHS-chemistry. [41][42][43] In this case, the functional group is attached on the lysine residues or the N-termini of the antibodies. This functionalization strategy is highly unspecific as lysine residues are distributed over the whole antibody sequence including the antigen-binding site (Fab region).…”
Section: Antibody Functionalization and Coupling To Liposomes Via Copmentioning
confidence: 99%
“…The average aspect ratio of the GNRs was 2.0. The electrostatic adsorption method establishing transferrin-coated GNRs was reported previously in the literature (36). 4 µL of 50 mM borate buffer (pH 8.5) and 5 µL of 3mg/mL transferrin (CAS:…”
Section: Methodsmentioning
confidence: 99%
“…Filbrun et al proposed a procedure for chemical modification of the lysine residues of antibodies before conjugation with gold nanoparticles and showed that it provided conjugates that were stable over a wide pH range [44]. Bauer et al [45] developed a technique for the preparation and use of antibody conjugates modified with histidine-rich peptides (called "capture and release" antibody reagents).…”
Section: Proper Receptor For Lfiamentioning
confidence: 99%